ЁШ АВЛОДГА ТАЪЛИМ ВА ТАРБИЯ БЕРИШДА ЎҚИТУВЧИНИНГ ИННОВАЦИОН ФАОЛИЯТИ ВА ТАЪЛИМ ТЕХНОЛОГИЯЛАРИ (E Conference Zone, 2022)
the article reflects the characteristics of modern teaching, interactive techniques, the role and impact of innovative technologies, technological map. Also, the basic principles, ways, methods, forms, means of effective organization of the educational process are identified. The most important thing is given scientific recommendations on the innovative activity of the teacher and educational technology